CHILD NURSE IMAGE FOR CHILDREN, THEIR PARENTS, PRE-SCHOOL TEACHERS AND NURSING STUDENTS - Ivanova, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article analyzes the literature on the historical aspect of the process of formation of the nursing specialty. The professional activity of nurses in modern care system is updated. An empirical study covers the criteria and indicators of the image of a nursing son. The content of the practical study reveals the ratings, vision, judgments about the duties of the nurses, their implementation, and their visual image for the children of children, their parents, preschool educational institutions and nursing school curriculum students.